A Unified Assessment Approach for Urban Infrastructure Sustainability and Resilience - Liang Wang; Xiaolong Xue; Zeyu Wang; Linshuang Zhang (Advances in Civil Engineering)
The concepts of sustainability and resilience have become very popular in the field of urban infrastructure. This paper reviews previous research on sustainability and resilience of urban infrastructure. The concepts of urban infrastructure’s sustainability and resilience are compared from the perspectives of dimensions, properties, goals, and methodologies. The paper systematically assesses the sustainability and resilience of urban infrastructure by using the concept of the grade point average (GPA). The GPA of urban infrastructure’s sustainability and resilience (urban infrastructure SR-GPA) is proposed as a unified concept. The assessment index system of urban infrastructure SR-GPA is constructed from five dimensions including demand, status, influence, resource, and measure. The analytic network process (ANP) is used to assess urban infrastructure SR-GPA considering the interaction between the indexes. The ANP structure model of urban infrastructure SR-GPA is established based on the assessment method and index system. The Harbin subway SR-GPA is selected as an empirical study to test the applicability of the proposed assessment method. The results show that the assessment indexes have different impacts on urban infrastructure SR-GPA. The Harbin subway SR-GPA is in a low level and can be upgraded through increasing construction investment, allocating resources efficiently, and considering resilience in the whole life cycle.